Direct uptake of sphingosine-1-phosphate independent of phospholipid phosphatases - Goto, Hirotaka (J Biol Chem, 2021)
Sphingosine-1-phosphate (S1P) is a lipid mediator that is relatively abundant in plasma and plays an important role in the vascular and immune systems. To date, the only known mechanism for removing S1P from plasma has been dephosphorylation by phospholipid phosphatases (PLPPs) on the surface of cells in contact with the plasma. However, there remains a possibility that PLPP-independent dephosphorylation or direct S1P uptake into cells could occur. To examine these possibilities, here we generated triple KO (TKO) HAP1 cells that lacked all PLPPs (PLPP1–3) present in mammals. In the TKO cells, the intracellular metabolism of externally added deuterium-labeled S1P to ceramide was reduced to 17% compared with the WT cells, indicating that most extracellular S1P is dephosphorylated by PLPPs and then taken up into cells. However, this result also reveals the existence of a PLPP-independent S1P uptake pathway. Tracer experiments using [(32)P]S1P showed the existence of a direct S1P uptake pathway that functions without prior dephosphorylation. Overexpression of sphingolipid transporter 2 (SPNS2) or of major facilitator superfamily domain containing 2B (MFSD2B), both known S1P efflux transporters, in TKO cells increased the direct uptake of S1P, whereas KO of MFSD2B in TKO cells reduced this uptake. These results suggest that these are channel-type transporters and capable of not only exporting but also importing S1P. Furthermore, we observed that erythroid cells expressing MFSD2B, exhibited high S1P uptake activity. Our findings describing direct S1P uptake may contribute to the elucidation of the molecular mechanisms that regulate plasma S1P concentration.